(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In this article the author marks merits of the great Kazakh writer, the academician of Academy of Sciences in Kazakhstan Mukhtar Auezov before the country and the Kazakh literature and opens its thematic, works of art and the genre features which have reached of high world level.